2022
DOI: 10.1186/s12911-022-02008-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of mobile phones for rehabilitative services among prosthetics users in rural Acholi sub-region of northern Uganda: findings from a qualitative study

Abstract: Background Digital technologies such as mobile phones have shown potential as vital tools for use in healthcare and related services. However, little has been done to explore its use for prosthetics rehabilitative services, especially in the Acholi sub-region of northern Uganda. We address this gap by exploring ownership of the mobile phone, knowledge of the use of mobile phone applications, use of mobile phones for prosthetics rehabilitative services and challenges faced in using the mobile ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Furthermore, the mobile phone was often switched off, discharged or the patient or relatives did not have the phone with them. Yagos et al (13) found similar challenges in the use of mobile phones within rehabilitation in Uganda such as lack of places for charging mobile phones, lack of electricity, inadequate skills to operate a mobile phone, and the high price for airtime. However, despite the challenges the participants in the present study were positive about using mobile phones in rehabilitation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, the mobile phone was often switched off, discharged or the patient or relatives did not have the phone with them. Yagos et al (13) found similar challenges in the use of mobile phones within rehabilitation in Uganda such as lack of places for charging mobile phones, lack of electricity, inadequate skills to operate a mobile phone, and the high price for airtime. However, despite the challenges the participants in the present study were positive about using mobile phones in rehabilitation.…”
Section: Discussionmentioning
confidence: 95%
“…E-health tools are mobile-and xed phones, text and multimedia messaging and voice over internet protocol, which encourage communication between patient and healthcare providers. There are several studies showing that ICT have a potential to improve healthcare and related services, e.g., a way for health professionals and patients to communicate, to spread knowledge about health, data collection, patient monitoring and other healthcare-related communication (11)(12)(13).…”
Section: E-healthmentioning
confidence: 99%
See 1 more Smart Citation
“…throughout Uganda, especially in remote regions of the country [38][39][40]. Consequently, it was assumed that mobile phone access equated to utilization in this inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, knowledge of the extent and amount of mobile phone usage and access by the women surveyed was limited in this study. Digital illiteracy, limited availability of chargers and electricity, expensive data and airtime costs, and unequal phone sharing have been documented throughout Uganda, especially in remote regions of the country [3840]. Consequently, it was assumed that mobile phone access equated to utilization in this inquiry.…”
Section: Discussionmentioning
confidence: 99%